Objective sleep outcomes 20 years after traumatic brain injury in childhood. Issue 17 (13th August 2020) - Botchway, Edith N.; Godfrey, Celia; Nicholas, Christian L.; Hearps, Stephen; Anderson, Vicki; Catroppa, Cathy
Abstract: Purpose: To assess objective sleep outcomes and correlates in young adults with a history of childhood traumatic brain injury. Materials and methods: Participants included 45 young adults who sustained brain injury in childhood (mild = 12, moderate = 22, and severe = 11) and 13 typically developing control participants. Sleep was assessed with actigraphy and sleep diaries recorded over 14 consecutive days. Rates of good sleep (sleep efficiency ≥ 85%) and poor sleep (sleep efficiency < 85%) were also evaluated. Results: At 20-years postinjury, participants with traumatic brain injury and controls presented with similar outcomes across the objective sleep parameters (all p  > 0.050) and rates of poor sleepers were also similar between these groups ( p  = 0.735): 67% and 77%, respectively. However, moderate and severe traumatic brain injury and female sex were associated with longer sleep duration. Conclusions: These findings provide preliminary insights into objective sleep outcome and associated factors in the very-long-term after childhood brain injuries. They also indicate the need to monitor sleep outcomes in young adults with and without traumatic brain injury. Implication for rehabilitation: Sustaining traumatic brain injury in childhood can impact on several functional domains including sleep. Sleep disturbances, particularly insomnia-related symptoms, are common in this population, with evidence of poor outcomes reported until adolescence postinjury, while outcomes beyond adolescence remain unexplored. In this first investigation of objective sleep outcomes in young adults with a history of childhood traumatic brain injury, we showed that insomnia-related symptoms are highly prevalent in both young adults with traumatic brain injury (67%) and healthy controls (77%). These findings suggest the need to routinely evaluate and treat sleep problem in young adults in general, irrespective of history of childhood traumatic brain injury.